Improvement of Hepatocyte Transplantation Efficiency in the mdr2–/– Mouse Model by Glyceryl Trinitrate. Issue 1 (January 2015) - Boudechiche, Lyes; Tranchart, Hadrien; Branchereau, Sophie; Davit-Spraul, Anne; Laïnas, Panagiotis; Groyer-Picard, Marie-Thérèse; Weber, Anne; Hadchouel, Michelle; Dagher, Ibrahim
Abstract : Introduction: Hepatocyte transplantation could be an alternative to liver transplantation for the treatment of metabolic diseases. However, rodent models have shown that engraftment of transplanted cells in the liver is low and requires deposition of cells in hepatic sinusoids. Splanchnic vasodilatators improved hepatocyte engraftment in a rat model. Therefore, we investigated the effect of glyceryl trinitrate (GTN) on the efficacy of cell engraftment and on liver repopulation in the mdr2-knockout mouse, a model for progressive familial intrahepatic cholestasis type 3. Methods: Congenic normal mdr2 (+/+) hepatocytes were isolated by two-step collagenase perfusion and transplanted into mdr2 (−/−) mice livers through the portal vein in the presence or absence of GTN. Liver repopulation was assessed by immunohistochemistry, and transplanted hepatocyte function was assessed at different times after transplantation by measurement of biliary lipid secretion and quantification of fibrosis. Results: The number of engrafted cells in GTN-treated mice was significantly higher than that in control mice, and transplanted hepatocytes were found in a greater number of distal sinusoids. Levels of phospholipid secretion were significantly higher than those in the control group 3 months after hepatocyte transplantation (18.3±2.3 vs. 5.2±3.9 nmol/min/100 g, P <0.0001), and the ratio of phospholipids to bile salt was greater (6.8±1.3 vs. 3.2±1.6, P =0.03). The percentage area of liver fibrosis was also significantly reduced in GTN-treated mice (5.7%±2.3% vs. 12.4%±2.9%, P =0.016). Conclusion: The use of GTN improves hepatocyte engraftment and correction of metabolic disease in mdr2 (−/−) mice. This approach might be beneficial in hepatocyte transplantation for the treatment of patients with liver diseases. Abstract : The use of a vasodilator improves wild-type hepatocyte engraftment in a genetic model of intrahepatic cholestasis, with concomitant improvements in phospholipid and bile salt production and hepatic histology.